Prevalence And Determinants of Anemia Among Adolescents in Coimbatore District, Tamil Nadu – A School Based Analytical Cross-Sectional Study - Shanmugam, Jeevithan; Kumar, Mohan; G, Dhanasekar; Ravikumar, Shruthi (National Journal of Community Medicine, 2023)
Context: The objective of the study was to estimate the prevalence of anemia among adolescents 10 to 19 years of age disaggregated by age group and gender. We also assessed the determinants of anemia among adolescents. Methods: An analytical cross-sectional study was carried out between July and November 2019 in a senior secondary public school, located in Coimbatore district, Tamil Nadu, India using a predesigned, semi-structured, pretested proforma that included haemoglobin estimation using oxyhemoglobin method. Results: The overall prevalence of anemia was 88.6% (95% CI 87.2 to 89.8); it was ten percent points higher in females (93.8%, 95% CI 92.1 to 95.1) compared to males (83.9%, 95% CI 81.7 to 85.8). Multivariate regression analysis showed that early adolescents (AOR 3.05, 95% CI 2.19 to 4.24), females (AOR 6.94, 95% CI 4.90 to 9.83), those with A or B or AB blood groups (AOR 2.58, 95% CI 1.92 to 3.49), physical inactivity (AOR 2.18, 95% CI 1.43 to 3.33) and attainment of menarche (AOR 2.69, 95% CI 1.73 to 4.21) were independent predictors of anemia in adolescents. Conclusion: It is the need of the hour to identify vulnerable groups; factors that predict occurrence, prioritize them to design and implement an effective public health action. Also, the effectiveness of existing strategies in the form of periodic deworming, Iron and Folic acid tablets (IFA) should be reassessed.